1999
DOI: 10.1088/0954-898x/10/4/302
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of experience-dependent plasticity in adult rat cortical barrel-column

Abstract: We model experience-dependent plasticity in the adult rat S1 cortical representation of the whiskers (the barrel cortex) which has been produced by trimming all whiskers on one side of the snout except two. This manipulation alters the pattern of afferent sensory activity while avoiding any direct nerve damage. Our simplified model circuitry represents multiple cortical layers and inhibitory neurons within each layer of a barrel-column. Utilizing a computational model we show that the evolution of the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Acute changes in RF might also be explained by other forms of synaptic plasticity. Hebbian synaptic plasticity (Hebb 1949) has been proposed as a mechanism for the maintenance of cortical RFs in several modalities (Pearson et al 1987; Armentrout et al 1994; Benuskova et al 1994; Jenison 1997; Benuskova et al 1999) and models of it can reproduce (Jenison 1997) the normal development of tonotopy (Reale et al 1987) and the changes following lesions reported by Robertson and Irvine (1989). Another possibility is that multineuron circuitry could result in processing that is functionally similar to that which we see in dendrites in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Acute changes in RF might also be explained by other forms of synaptic plasticity. Hebbian synaptic plasticity (Hebb 1949) has been proposed as a mechanism for the maintenance of cortical RFs in several modalities (Pearson et al 1987; Armentrout et al 1994; Benuskova et al 1994; Jenison 1997; Benuskova et al 1999) and models of it can reproduce (Jenison 1997) the normal development of tonotopy (Reale et al 1987) and the changes following lesions reported by Robertson and Irvine (1989). Another possibility is that multineuron circuitry could result in processing that is functionally similar to that which we see in dendrites in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Given the remarkable spatial relationship between the whisker and its associated barrel column, it is surprising that, with the exception of refs. [65], [66] and our own previous model [44], connection geometry has not been an important factor in computational neuroscience models of the barrel system.…”
Section: Discussionmentioning
confidence: 76%
“…The inputs from cut whiskers were assumed to relay noise for 100% of time steps, i.e., d i vpm (t) ϭ n i vpm (t) and d i cor (t) ϭ n i cor (t) for i ϭ D-cut (D3), C2, and E2. The level (or amplitude) of noise plays an important role in synaptic modification according to the Bienenstock, Cooper, Munro (BCM) theory because it determines the magnitude of decrease of synaptic weights when the cell response c is below M and close to zero (7,20). The two spared whiskers, D2 and D1, were ''stimulated'' at random, either both at once or each one alone.…”
Section: (T) ϭ ͚M I (T)d I (T) According To Intrator and Cooper (19)mentioning
confidence: 99%
“…We have found that circuitry within the adult rat barrel cortex is modified by innocuous changes in whisker experience in accordance with the BCM rules of synaptic plasticity (3)(4)(5)(6)(7). Any model for activity-dependent plasticity in cortex must satisfy the central concept of adequate intracellular calcium entry through depolarization-dependent calcium permeable receptors, which in turn induce a cascade of molecular changes leading to LTP or LTD (2).…”
mentioning
confidence: 95%